Diagnostic and Epidemiological study of Blastocystis hominis in Samarra city, Iraq - Omaima I. Mahmood; Thu-Alfaqar A. Khudher; Thu-Alfaqar A. Khudher (Tikrit Journal of Pure Science)
The present study included detection of infection with Blastocystis hominis in Sammara city / Salah Al-Deen province , from April 2014 until April 2015. 264 stool samples were collected from children less than 15 years old which attending the General hospital and some medical laboratories in the city. Microscopic examination by using trichrome stain was used to detected this parasite. By using trichrome stain, cyst and vacuolar forms the only stages had been distinguished. The results of study revealed the rate of infection was (15.15%) by using microscopic examination. Epidemiological survey demonstrated there is no significant differences between male and female and more frequently infected at the (6-10) years age group (21.9%) and (13.33%). Also the higher rate of infection was during Spring, and the lower rate was in Autumn. Single infection with B.hominis was (9.09%), but the mixed infection with the other parasite was (3.78%) with E. histolytica and (2.27%) with G. lamblia. Diarrhea was the distinguish sign with infection children.